Faktor-Faktor Yang Berhubungan Dengan Penggunaan Alat Kontrasepsi Dalam Rahim (AKDR) Di Wilayah Kerja Puskesmas Kabun Kabupaten Rokan Hulu Tahun 2013 - Aldriana, Nana (Jurnal Martenity and Neonatal, 2013)
IUD is one of ideal non-hormonal contraception to control pregnancies, but the use of IUDs in Indonesia is still lower than other contraception method. The used of IUD decrease from 6,2% (SDKI 2002/03), to 4,9% (SDKI 2007) and fell down to 3,9% (SDKI 2012). In Rokan Hulu districs the used of IUD are 0,9% (2011) and 1,2% (2012). In work area of Kabun Health Center, there are 356 (7.2%) people who used IUD. This research aims to know the associated factors the use of IUDs. The research is quantitatives analytic with case control study designed. Number of sample is 440 person selected by proportionalm sampling. Data analysis is perform using univariate, bivariate chi-square test and multivariate multiple logistic regression. The result are, husband’s support : OR 9,371 (95% CI = 5.9-14.6), the number of living children : OR 3,182 (95% CI = 2.0-4.8), knowledge OR 2,979 (95% CI = 2.0-4.4), attitude of health workers : OR 2,010 (95% CI = 1.3-2.9), maternal age : OR 1,788 (95% CI = 1.2-2.6), ease of reaching IUD services facilities : OR 1,368 (95% CI = 0.8-2.2), education : OR 1,058 (95% CI = 0.7-1.5), occupation : OR 0,774 (95% CI = 0.5-1.1), rumors : OR 0,952 (95% CI = 0.5-1.7). The conclusion is that there is relationship between the husband’s support, the number of living children, knowledge and attitude of health workers with the use of IUDs, thus it suggestion that the husband supports the use of IUDs and health workers to be positive especially to low maternal knowledeable about IUDs and had more than two children.